Interaction in metal rare gas complexes and assignment of REMPI spectra of some disubstituted benzenes - Zheng, Yu (2018)
A consistent set of interaction energy curves are shown in this work for the Group 2 (IIA) and Group 12 (IIB) metal cation/rare gas complexes, M+ RG, where M+ = Be+–Ra+ and Zn+–Hg+; and RG = He–Rn. spectroscopic constants derived from these are reported and compared with available data, and discuss trends in the values. Insight into the interactions are gained that occur using a range of approaches: reduced potential energy curves; charge and population analyses; molecular orbital diagrams and contour plots; and Birge-Sponer plots. Although sp hybridisation occurs in the Be+ RG, Mg+ Rg and Group 12 M+ RG complexes, this appears to be minimal and covalency is the main aspect of the interaction. However, major sd hybridisation occurs in the heavier Group 2 M+ RG systems, which increases their interaction energies but there is minimal covalency. Examination of Birge-Sponer plots reveals significant curvature in many cases, which are ascribed to the changing amounts of hybridisation or covalency as a function of internuclear separation. This suggests why the use of a simple electrostatics-based model potential to describe the interactions is inadequate. Assignment of four different spectra obtained by resonance-enhanced multiphoton ionisation spectroscopy (REMPI) is undertaken; these are for the four disubstituted benzene molecules: ortho-difluorobenzene, ortho-chlorofluorobenzene, meta–difluorobenzene and meta- chlorofluorobenzene . Comparing with several previous experimental studies, some results could be compared,and confirms the correctness of the analysis. More generally, the information impacts on how mixed the vibrational motions have become – this directly impacts on how well energy can be dispersed in each molecule.